Harnessing Photoredox and Weak Brønsted Base Dual Catalysis for Selective C(sp3)–H Bond Activation - Atriardi, Shafrizal R.; Anita, Yulia; Woo, Sang Kook (Synthesis, 2024)
Visible light photoredox and weak Brønsted base dual catalysis has emerged as a powerful and versatile tool in the activation of C(sp3)–H bonds under mild reaction conditions. This method allows for the selective functionalization of a wide range of substrates, including amines, sulfides, ethers, dithianes and dithiolanes, dioxolanes, and alkenes. By exploiting the increased acidity of C–H bonds following single electron oxidation, this strategy employing a dual catalyst facilitates various carbon–carbon bond-forming reactions, as well as selective rearrangements, with high efficiency and regioselectivity. This review highlights recent advancements in this field, emphasizing the underlying mechanisms and the broad applicability of these methodologies in organic synthesis.1 Introduction2 Activation of α-C(sp3)–H Bonds in N-, S-, and O-Containing Compounds for C–C Bond Formation3 Activation of Allylic C–H Bonds for C–C Bond Formation4 Photoredox and Base Dual Catalysis for Rearrangement Reactions5 Conclusion
Keywords: photoredox; weak Brønsted base; dual catalysis; single electron oxidation; C(sp3)–H bond activation